Klasifikasi Kinerja Pegawai Universitas X dengan pendekatan Neuro-Fuzzy - Ronald Dwi Nompunu; Purnomo Budi Santosa; Erni Yudaningtyas (Jurnal EECCIS, 2018)
Abstract—classification of employee performance of university x is the basis of policy recommendation of career system, this is done every year with certain method, the use of this method to estimate classification of employee performance still have high uncertainty level, because of weight and sub-variable of assessment is fluctuate. So that required klasfikasi performance system for employee forecasting that is closer to certainty. in this study a classification system is made by using a combination of neural network and fuzzy logic (Neuro-Fuzzy) for better accuracy level, through Hybrid Neuro Fuzzy optimization obtained by smaller RMSE value, based on Neuro-Fuzzy ratio and other methods with evaluation obtained value accuracy 89% Index Terms —Classification, staf performance, Neuro-Fuzzy, Hybrid